INTERVENÇÃO ALIMENTARE EM MULHERES PÓS-MENOPAUSA COM SOBREPESO E OBESIDADE EM SEUS DOMICÍLIOS - Turcato, Marlon; Franz, Ligia B. B.; Zanetti, Carolina; Conte, Francieli; Boff, Viviane S.; Wassermann, Emanuele R. (Salão do Conhecimento, 2013)
Resumo